Repetitive Transcranial Magnetic Stimulation Elicits Antidepressant- and Anxiolytic-like Effect via Nuclear Factor-E2-related Factor 2-mediated Anti-inflammation Mechanism in Rats. (1st March 2020) - Tian, Li; Sun, Si-Si; Cui, Long-Biao; Wang, Shi-Quan; Peng, Zheng-Wu; Tan, Qing-Rong; Hou, Wu-Gang; Cai, Min
Highlights: TMS ameliorated depressive and anxiety behavior induced by CUMS in rats. The attenuation of neuroinflamamtion participated the antidepressant- and anxiolytic- like effect of rTMS. Nrf2 activation mediated the anti-inflammation mechanism produced by rTMS. Abstract: Repetitive transcranial magnetic stimulation (rTMS) treatment is widely accepted as an evidence-based treatment option for depression and anxiety. However, the underlying mechanism of this treatment maneuver has not been clearly understood. The chronic unpredictable mild stress (CUMS) procedure was used to establish depression and anxiety-like behavior in rats. The rTMS was performed with a commercially available stimulator for seven consecutive days, and then depression and anxiety-like behaviors were subsequently measured. The expression of nuclear factor-E2-related factor 2 ( Nrf2) was measured by western-blot, and the level of tumor necrosis factor-α (TNF-α), inducible nitric oxide synthase (iNOS), interleukin-1β (IL-1β), and interleukin-6 (IL-6) was measured with Enzyme-linked immunesorbent assay (ELISA) analyzing kits. Furthermore, a small interfering RNA was employed to knockdown Nrf2, after which the neurobehavioral assessment, Nrf2 nuclear expression, and the amount of inflammation factors were evaluated. Application of rTMS exhibited a significant antidepressant and anxiolytic-like effect, which was associated with the increased Nrf2 nuclear translocation and reduced level of TNF-α, iNOS, IL-1β, and IL-6 in the hippocampus. Following Nrf2 silencing, the antidepressant and anxiolytic-like effect produced by rTMS was abolished. Moreover, the elevated Nrf2 nuclear translocation, and the reduced production of TNF-α, iNOS, IL-1β, and IL-6 in hippocampus mediated by rTMS, were reversed by Nrf2 knockdown. Together, these results reveal that the Nrf2-induced anti-inflammation effect is crucial in regulating antidepressant-related behaviors produced by rTMS.